PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI HOBBY COFFEE KOTA BATAM - Dwi Eka Syahputri; Dailami (JURNAL MENATA, 2023)
This research aims to determine the effect of service quality on customer satisfaction at Hobby Coffee Batam. Data was collected by distributing questionnaires. The type of research used is quantitative research. The number of samples set in this study were 100 respondents. The sampling technique used is random sampling technique. The research data collection method was carried out by distributing questionnaires using a five-point Likert scale as a measuring tool.